Sangiovese cv Pomace Seeds Extract-Fortified Kefir Exerts Anti-Inflammatory Activity in an In Vitro Model of Intestinal Epithelium Using Caco-2 Cells - Gabriele Carullo; Paolo Governa; Umile Gianfranco Spizzirri; Marco Biagi; Fabio Sciubba; Gianluca Giorgi; Monica Rosa Loizzo; Maria Enrica Di Cocco; Francesca Aiello; Donatella Restuccia (MDPI AG, 2020)
Inflammatory bowel disease and food allergies are a growing topic in the field of nutrition science. Polyphenols, which are the most important secondary metabolites of plants, demonstrated to modulate the expression and/or production of numerous proteins, but also to regulate the intestinal ecosystem. In this context, our aim was the investigation of protective effects against the gastrointestinal mucosa of fortified milk kefir obtained by adding seeds extract from Sangiovese cv. Pomace. Methods: An ultrasound-assisted method was used to obtain the extracts. All the extracts were assayed for the antioxidant activity. The best extract was used as an additive of fermented milk kefir to obtain a fortified final product. Kefir samples were analyzed by NMR spectroscopy. The efficiency of the barrier functions was evaluated by measuring trans-epithelial electric resistance (TEER) using a voltmeter. Results: the enriched kefir (Ksgn) possesses higher antioxidant performances compared to the unfortified sample (Kwht). Kwht and Ksgn did not alter Caco-2 TEER in basal condition.